Method for generating Li2Si2O5 protective layer on surface of positive electrode material
By forming a double -layer covering structure of LI2Si2O5 and SIO2 on the surface of the ion battery positive material, the problem of lithium ion battery failure in high temperature environments is solved, and the electrochemical properties of the material and fast charging and fast release capabilities are improved.
Patent Information
- Application Number
- CN202411960000.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-01-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing lithium-ion battery positive electrode materials are prone to failure in high temperature environments, and conventional lithium silicate Li2SiO3 cannot effectively reduce the internal resistance of the material and improve fast charging and fast release performance.
By controlling the amount of SiO2, SiO2 directly covers the three -yuan positive material substrate, absorb residual lithium in SIO2 in contact with the surface of the substrate, forms a LI2Si2O5 cover layer. Essence
It improves the electrochemical performance of positive materials, improves lithium ion conductivity, reduces the internal resistance of the material, and enhances the stability and fast charging and fast -lip performance in high temperature environments.
Smart Images

Figure CN119381440A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium ion batteries, and in particular to a method for generating a Li2Si2O5 protective layer on the surface of a positive electrode material. Background Art
[0002] As one of the hottest research directions in the current battery industry, fast-charge and fast-discharge lithium-ion batteries are an effective means to solve the current problems of insufficient endurance and long charging time for low-altitude aircraft. However, fast-charge and fast-discharge lithium-ion batteries are prone to failure in high-temperature environments, and better thermal management measures are needed to ensure the safety of the batteries. At the same time, higher requirements are placed on the positive electrode materials used. Not only must they have the ability to quickly deintercalate lithium ions, but they must also solve problems such as cycle deterioration under high-power charging and discharging, and severe heating caused by excessive internal resistance. Conventional lithium silicate Li2SiO3 can also protect the surface of the positive electrode material, but its ionic conductivity is low, and it cannot reduce the internal resistance of the material and improve the fast-charge and fast-discharge performance of the material. Lithium disilicate Li2Si2O5 has an orthorhombic crystal structure, which is composed of corner-shared SiO4 tetrahedrons and Li + Composition, amorphous Li2Si2O5 opens quite a few minimum energy channels, Li + Good lithium ion conductivity can be achieved by hopping along the channel from adjacent SiO4 layers.
[0003] Prior art 1: Chinese patent application 201710187387.X discloses a double-layer coated lithium-ion battery positive electrode material and a preparation method thereof, in which a double-layer coating of a silicon lithium salt coating layer and a metal oxide coating layer is used to prevent the substrate from being corroded by the electrolyte, and the formation of the silicon lithium salt coating layer can reduce the residual lithium on the surface of the substrate, so that the obtained positive electrode material has high rate performance, high specific capacity and good cycle performance.
[0004] However, in this scheme, the silicon lithium salt coating layer is formed by wet coating the substrate with silicon weak acid and solvent. In this process, the amount of solvent added during wet coating also needs to be controlled, and the solvent needs to be treated accordingly after coating, which makes the operation more complicated.
[0005] Through research, the present application has found that by using SiO2 to directly coat the substrate in the form of dry coating, it is only necessary to control the amount of SiO2 added. Not only can SiO2 react with the residual lithium on the surface of the substrate to generate a Li2Si2O5 coating layer, but the remaining SiO2 formed from the first coating layer can also form a SiO2 coating layer, thereby forming a double-layer coating structure on the surface of the substrate and improving the electrochemical properties of the substrate.
[0006] The problem that this proposal needs to solve: How to propose a method for preparing a ternary positive electrode material. Summary of the invention
[0007] The purpose of the present invention is to provide a method for generating a Li2Si2O5 protective layer on the surface of a positive electrode material. By controlling the amount of SiO2 added, the SiO2 is directly coated on a ternary positive electrode material matrix. The SiO2 in contact with the matrix surface absorbs residual lithium on the matrix surface to form a Li2Si2O5 coating layer, and the remaining SiO2 that forms the first coating layer forms a SiO2 coating layer, thereby forming a double-layer coating to improve the electrochemical performance of the positive electrode material.
[0008] To achieve the above-mentioned purpose, the present application discloses a ternary positive electrode material, which is composed of a substrate, a first coating layer coated on the surface of the substrate, and a second coating layer coated on the surface of the first coating layer; The first coating layer is a Li2Si2O5 coating layer; The second coating layer is a SiO2 coating layer.
[0009] The first coating layer is formed by the reaction of SiO2 and residual lithium on the surface of the substrate; The second coating layer is formed by the SiO2 remaining from the reaction of the first coating layer with the residual lithium on the surface of the substrate.
[0010] The ternary positive electrode material matrix is directly coated with SiO2, and the SiO2 in contact with the matrix surface absorbs the residual lithium on the matrix surface to form a Li2Si2O5 coating layer, while the remaining SiO2 that forms the first coating layer forms a SiO2 coating layer, thereby forming a double-layer coating and improving the electrochemical performance of the positive electrode material.
[0011] Preferably, the specific operation of forming the first coating layer and the second coating layer is: putting SiO2 and the substrate into a mixer for mixing, and then sintering, cooling, crushing, and sieving to obtain a ternary positive electrode material containing a double coating layer; The mass of Si element in the SiO2 is 0.3% to 0.5% of the mass of the matrix; The D50 particle size of the matrix is 5 to 8 μm.
[0012] By controlling the amount of SiO2 added and the D50 particle size of the matrix, the silica can be better evenly coated on the particle surface.
[0013] Preferably, the rotation speed of the mixer is: first at 20-100 rpm for 5-10 min, and then at 500-800 rpm for 15-25 min.
[0014] In addition, a method for preparing the above-mentioned ternary positive electrode material is also disclosed, comprising the following steps: Step 1: Mixing, pre-sintering, cooling, crushing and screening the ternary precursor, lithium source and metal hydroxide to obtain a matrix; Step 2: Put SiO2 and the matrix into a mixer for mixing, and then sinter, cool, crush and sieve to obtain a ternary positive electrode material containing a double coating layer.
[0015] Preferably, the ternary precursor is Ni x Co y Mn z M 1-x-y-z (OH)2, of which 0.5 <x<0.65,0.2<y<0.3,0.045<z<0.295; The M element is selected from Ti, Zr, Ce, Sn or W; By in-situ doping of the M element in the precursor, the uniformity of doping can be improved and the interface bonding strength can be enhanced. At the same time, by controlling the doping amount of the M element, the cycle stability and thermal stability of the fast-charging and fast-discharging ternary positive electrode material can be better guaranteed.
[0016] Preferably, the lithium source is lithium carbonate, and the molar ratio of lithium element in the lithium source to the metal element in the ternary precursor is 1.01 to 1.10; The metal hydroxide is selected from at least one of sodium hydroxide, magnesium hydroxide and aluminum hydroxide, and the mass of the metal element is 1000-2000ppm of the mass of the ternary precursor; By controlling the Li source to be lithium carbonate, it is ensured that the residual lithium on the surface of the material after the first sintering is mainly lithium carbonate, so that it can fully react with silicon dioxide to form a Li2Si2O5 coating layer.
[0017] The purpose of adding the above-mentioned metal hydroxide during the sintering process is to embed the dopant into the Li layer at the same time during the lithium insertion process, thereby widening the Li channel and improving the fast charging and discharging capability of the material.
[0018] Further preferably, the molar ratio of the lithium element in the lithium source to the metal element in the ternary precursor is 1.03 to 1.06; By controlling the molar ratio of lithium to metal elements in the ternary precursor, more lithium ion deintercalation sites can be provided to ensure the fast charging and discharging capabilities of the material. At the same time, the material will not undergo excessive structural changes during the fast charging and discharging process, which will accelerate the cycle deterioration.
[0019] Preferably, the specific operation of the pre-sintering is: firstly heating to 650-750°C at 2-5°C / min and keeping it at that temperature for 3-5 hours; then heating to 850-950°C at 2-3°C / min and keeping it at that temperature for 10-16 hours; then cooling to 650-750°C at 3-5°C / min and keeping it at that temperature for 1-3 hours; By adding a low-temperature repair platform after high-temperature sintering, the lattice defects caused by high-temperature sintering of the material can be repaired, and the component segregation, especially the segregation of doping elements and Li, can be reduced, which leads to poor electrochemical properties of the material.
[0020] Preferably, the specific steps of sintering in step 2 are: heating to 400-500° C. at 2-3° C. / min, and keeping the temperature for 8-12 hours; Reference Figure 4 It can be seen that the reaction temperature of lithium carbonate and silicon dioxide is between 400 and 500°C, so the secondary sintering temperature can be adjusted to control the formation of surface coatings. When the temperature is below 400°C, lithium carbonate and silicon dioxide are difficult to react. When the temperature is above 500°C, the thermal motion of lithium atoms in the lattice intensifies, and their activity increases significantly, making it easier to overcome the constraints of the lattice energy and de-embed from the lattice, resulting in poor capacity and rate performance of the material.
[0021] The beneficial effects of the present invention are: The present invention provides a preparation method and application of organic complex-coated lithium manganate, in which a ternary positive electrode material substrate is directly coated with SiO2, and the SiO2 in contact with the substrate surface absorbs residual lithium on the substrate surface to form a Li2Si2O5 coating layer, while the remaining SiO2 forming the first coating layer forms a SiO2 coating layer, thereby forming a double-layer coating to improve the electrochemical performance of the positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a scanning electron microscope image of the ternary positive electrode material prepared in Example 1; Figure 2 This is the Si energy spectrum of the ternary cathode material prepared in Example 1; Figure 3 The XRD spectrum of the ternary cathode material prepared in Example 1; Figure 4 These are TG diagrams of lithium carbonate, silicon dioxide, and a mixture of lithium carbonate and silicon dioxide, where Li2CO3 is a pure lithium carbonate sample, SiO2 is a pure silicon dioxide sample, Li2CO3-SiO2-43 is a mixture of lithium carbonate and silicon dioxide in a molar ratio of 4:3, and Li2CO3-SiO2-73 is a mixture of lithium carbonate and silicon dioxide in a molar ratio of 7:3. DETAILED DESCRIPTION
[0023] In the description of the present invention, it should be noted that, if the specific conditions are not specified in the examples, the experiments were carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be purchased commercially.
[0024] Example 1 Step 1: Ni 0.6 Co0.25 Mn 0.14 Ti 0.01 (OH )2 , lithium carbonate is mixed at a metal element molar ratio of Li / (Ni+Co+Mn+Ti)=1.05, and then sodium hydroxide with a sodium element mass of 1500ppm of the mass of the ternary precursor is added and mixed, and then the temperature is raised to 700℃ at 3.5℃ / min and kept warm for 4 hours; then the temperature is raised to 900℃ at 2.5℃ / min and kept warm for 13 hours, and then the temperature is lowered to 700℃ at 4℃ / min and kept warm for 2h, cooled, crushed, and sieved to obtain a matrix with a D50 particle size of 6.5μm; Step 2: Mix the matrix and SiO2 with Si element accounting for 0.15% of the matrix mass in a high-speed mixer at 50 rpm for 7 minutes, then at 600 rpm for 20 minutes, then heat to 470°C at 2.5°C / min, keep warm for 10 hours, crush and sieve to obtain a ternary positive electrode material with a double coating layer and a D50 particle size of 6.5 μm.
[0025] Example 2 Step 1: Ni 0.6 Co 0.25 Mn 0.14 Ti 0.01 (OH )2 , lithium carbonate is mixed at a metal element molar ratio of Li / (Ni+Co+Mn+Ti)=1.03, and then sodium hydroxide with a sodium element mass of 1500ppm of the ternary precursor mass is added and mixed, and then the temperature is raised to 650°C at 2°C / min and kept warm for 5 hours; then the temperature is raised to 850°C at 2°C / min and kept warm for 16 hours, and then the temperature is lowered to 650°C at 3°C / min and kept warm for 3 hours, cooled, crushed, and sieved to obtain a matrix with a D50 particle size of 6.5μm; Step 2: Mix the matrix and SiO2 with Si element accounting for 0.15% of the matrix mass in a high-speed mixer at 20 rpm for 10 min, then at 500 rpm for 25 min, then heat to 350°C at 2°C / min, keep warm for 12 h, crush and sieve to obtain a ternary positive electrode material with a double coating layer and a D50 particle size of 6.5 μm.
[0026] Example 3 Step 1: Ni 0.6 Co 0.25 Mn 0.14 Ti 0.01 (OH )2, lithium carbonate is mixed at a metal element molar ratio of Li / (Ni+Co+Mn+Ti)=1.06, and then sodium hydroxide with a sodium element mass of 1500ppm of the ternary precursor mass is added and mixed, and then the temperature is raised to 750℃ at 5℃ / min and kept warm for 3 hours; then the temperature is raised to 950℃ at 3℃ / min and kept warm for 10 hours, and then the temperature is lowered to 750℃ at 5℃ / min and kept warm for 1h, and then cooled, crushed and sieved to obtain a matrix with a D50 particle size of 6.5μm; Step 2: Mix the matrix and SiO2 with Si element accounting for 0.15% of the matrix mass in a high-speed mixer at 100 rpm for 5 min, then mix at 800 rpm for 15 min, then heat to 550°C at 3°C / min, keep warm for 8 h, crush and sieve to obtain a ternary positive electrode material with a double coating layer and a D50 particle size of 6.5 μm.
[0027] Example 4 It is basically the same as Example 1, except that the mass of the Si element in the SiO2 is 0.3% of the mass of the matrix.
[0028] Example 5 It is basically the same as Example 1, except that the mass of the Si element in the SiO2 is 0.5% of the mass of the matrix.
[0029] Example 6 It is basically the same as Example 1, except that the mass of the Si element in the SiO2 is 0.2% of the mass of the matrix.
[0030] Example 7 It is basically the same as Example 1, except that the mass of the Si element in the SiO2 is 0.6% of the mass of the matrix.
[0031] Example 8 It is basically the same as Example 1, except that the D50 particle size of the matrix is 5 μm.
[0032] Example 9 It is basically the same as Example 1, except that the D50 particle size of the matrix is 8 μm.
[0033] Example 10 It is basically the same as Example 1, except that the D50 particle size of the matrix is 9 μm.
[0034] Embodiment 11 It is basically the same as Example 1, except that the D50 particle size of the matrix is 4 μm.
[0035] Example 12 It is basically the same as Example 1, except that the ternary precursor is Ni0.6 Co 0.25 Mn 0.14 Zr 0.01 (OH)2.
[0036] Example 13 It is basically the same as Example 1, except that the ternary precursor is Ni 0.6 Co 0.25 Mn 0.15 (OH )2 .
[0037] Embodiment 14 Step 1: Ni 0.6 Co 0.25 Mn 0.15 (OH)2 and lithium carbonate are mixed at a metal element molar ratio of Li / (Ni+Co+Mn)=1.05, and then sodium hydroxide with a sodium element mass of 1500ppm of the mass of the ternary precursor and titanium dioxide with a titanium element mass of 5000ppm of the mass of the ternary precursor are added and mixed, and then the temperature is increased to 700℃ at 3.5℃ / min and kept warm for 4 hours; then the temperature is increased to 900℃ at 2.5℃ / min and kept warm for 13 hours, and then the temperature is decreased to 700℃ at 4℃ / min and kept warm for 2h, cooled, crushed, and sieved to obtain a matrix with a D50 particle size of 6.5μm; Step 2: Mix the matrix and SiO2 with Si element accounting for 0.15% of the matrix mass in a high-speed mixer at 50 rpm for 7 minutes, then at 600 rpm for 20 minutes, then heat to 470°C at 2.5°C / min, keep warm for 10 hours, crush and sieve to obtain a ternary positive electrode material with a double coating layer and a D50 particle size of 6.5 μm.
[0038] Embodiment 15 The method is basically the same as Example 1, except that lithium hydroxide of the same mass is used instead of lithium carbonate as the lithium source.
[0039] Example 16 The method is basically the same as Example 1, except that the metal hydroxide in step 1 is magnesium hydroxide.
[0040] Embodiment 17 The method is basically the same as Example 1, except that no metal hydroxide is added in step 1.
[0041] Embodiment 18 Step 1: Ni 0.6 Co 0.25 Mn 0.14 Ti 0.01 (OH )2, lithium carbonate is mixed at a metal element molar ratio of Li / (Ni+Co+Mn+Ti)=1.05, and then sodium hydroxide with a sodium element mass of 1500ppm of the mass of the ternary precursor is added and mixed, and then the temperature is raised to 700°C at 3.5°C / min and kept warm for 4 hours; then the temperature is raised to 900°C at 2.5°C / min and kept warm for 13 hours, cooled, crushed, and sieved to obtain a matrix with a D50 particle size of 6.5μm; Step 2: Mix the matrix and SiO2 with Si element accounting for 0.15% of the matrix mass in a high-speed mixer at 50 rpm for 7 minutes, then at 600 rpm for 20 minutes, then heat to 470°C at 2.5°C / min, keep warm for 10 hours, crush and sieve to obtain a ternary positive electrode material with a double coating layer and a D50 particle size of 6.5 μm.
[0042] Embodiment 19 It is basically the same as Example 1, except that the sintering temperature in step 2 is 300°C.
[0043] Embodiment 20 It is basically the same as Example 1, except that the sintering temperature in step 2 is 550°C.
[0044] Comparative Example 1 Step 1: Ni 0.6 Co 0.25 Mn 0.14 Ti 0.01 (OH )2 , lithium carbonate is mixed at a metal element molar ratio of Li / (Ni+Co+Mn+Ti)=1.05, and then sodium hydroxide with a sodium element mass of 1500ppm of the mass of the ternary precursor is added and mixed, and then the temperature is raised to 700℃ at 3.5℃ / min and kept warm for 4 hours; then the temperature is raised to 900℃ at 2.5℃ / min and kept warm for 13 hours, and then the temperature is lowered to 700℃ at 4℃ / min and kept warm for 2h, cooled, crushed, and sieved to obtain a matrix with a D50 particle size of 6.5μm; Step 2: The matrix and disilicate containing 0.245% Si element based on the matrix mass were mixed in a high-speed mixer at 50 rpm for 7 min and then at 600 rpm for 20 min. The coating material was heated to 450°C at 2.5°C / min, kept warm for 10 h, crushed, and sieved to obtain a ternary positive electrode material containing a single coating layer with a D50 particle size of 6.5 μm. Step 3: Mix the ternary positive electrode material containing a single coating layer with silicon dioxide containing Si element as 0.155% of the matrix mass in a high-speed mixer at 50 rpm for 7 minutes and then at 600 rpm for 20 minutes. Then, heat the coating material to 450°C at 2.5°C / min, keep it warm for 10 hours, crush it, and sieve it to obtain a ternary positive electrode material containing a double coating layer with a D50 particle size of 6.5μm.
[0045] Performance Testing Residual lithium test: Calculate lithium carbonate and lithium hydroxide in the material filtrate by potentiometric titration based on hydrochloric acid consumption; Capacity / 3.0-4.3V test: At room temperature, charge the battery at 0.1C / 5C, 4.3V constant current and constant voltage to the capacity of 0.01C / 0.5C cut-off current, and discharge the battery at 0.1C / 5C constant current from 4.3V to the capacity of 3.0V cut-off voltage; 100-cycle retention rate / 3.0-4.3V test: At room temperature 25°C, the capacity ratio of 50 cycles of 5C charge and discharge to the first cycle; 100 power-on cycle retention rate / 3.0-4.3V test: At high temperature of 45°C, the power is charged and discharged at 5C for 50 cycles and the capacity ratio of the first cycle.
[0046] The performance of the ternary positive electrode materials containing double coating layers prepared in the examples and comparative examples is shown in Table 1: Table 1 Group Residual lithium 5C charging capacity / 0.1C charging capacity (%) 5C discharge capacity / 0.1C discharge capacity (%) 50-week 5C cycle retention rate / % 50-week high temperature cycle retention rate at 5C without power on / % Example 1 Matrix 3750 77.5 78.4 80.5 75.6 Example 1 520 83.4 87.2 96.2 93.8 Example 2 523 83.2 87.0 96.5 93.0 Example 3 536 83.2 86.9 96.1 93.5 Example 4 530 83.1 87.0 95.7 92.1 Example 5 522 82.8 86.3 96.5 94.5 Example 6 1560 79.9 81.2 89.7 88.8 Example 7 523 80.6 84.5 96.4 94.1 Example 8 538 83.9 87.6 96.1 93.6 Example 9 526 83.2 86.7 95.2 92.7 Example 10 568 78.8 82.4 95.2 93.1 Embodiment 11 605 82.1 86.0 91.1 89.4 Example 12 521 83.5 87.3 96.3 94.2 Example 13 538 83.8 87.5 92.3 89.6 Embodiment 14 546 83.1 86.9 93.6 91.1 Embodiment 15 2227 81.6 83.1 91.9 89.4 Example 16 530 84.2 87.8 96.0 93.9 Embodiment 17 539 81.6 85.5 95.6 93.0 Embodiment 18 525 82.4 86.6 94.2 90.8 Embodiment 19 2589 78.5 80.1 91.3 87.9 Embodiment 20 1326 79.2 81.2 92.5 88.2 Comparative Example 1 1220 82.6 86.0 92.1 89.3
[0047] Conclusion analysis: 1. It can be seen from Examples 1-3 that when the process parameters of pre-sintering and sintering, the mixing rate and time of the mixer in the production process of the ternary positive electrode material are changed, the performance of the ternary positive electrode material will also be affected. Therefore, it can be seen that the implementation parameters in Example 1 are the optimal parameters; And from Figure 1-3 It can be seen from the scanning electron microscope image and Si energy spectrum of the ternary positive electrode material prepared in Example 1 that SiO2 is uniformly coated on the surface of the substrate on the surface of the ternary positive electrode material; and from the XRD spectrum of the ternary positive electrode material, it can be seen that only the characteristic peak of Li2Si2O5 appears in the XRD spectrum, which shows that the first coating layer of the ternary positive electrode material prepared in Example 1 is formed by Li2Si2O5.
[0048] 2. It can be seen from Examples 1 and 4-5 that when the particle size of the ternary cathode material matrix is consistent, when the amount of SiO2 added is changed, due to the change in the amount of SiO2, the thickness of the second coating layer formed by the reaction of the first coating layer with the residual lithium on the surface of the matrix and the remaining SiO2 will also change, thereby affecting the performance of the ternary cathode material; Further observation of Examples 6-7 shows that when the amount of SiO2 added is further reduced, SiO2 is not enough to completely react with the amount of residual lithium that can react on the surface of the substrate. Although most of the performance of the ternary positive electrode material can be slightly improved, the 5C / 0.1C charge and discharge capacity shows a downward trend. This is because when the amount of silicon dioxide is insufficient, conventional lithium silicate Li2SiO3 will be generated, which can also protect the surface of the positive electrode material, but its ionic conductivity is low, and it is impossible to reduce the internal resistance of the material and improve the fast charging and discharging performance of the material; and when the amount of SiO2 added is further increased, the residual lithium that can react on the surface of the substrate can be completely reacted to generate lithium disilicate Li2Si2O5, and its 5C / 0.1C charge and discharge capacity shows an upward trend, but when the amount of SiO2 is too much, compared with the ternary positive electrode material obtained in Example 1, its cycle performance is improved, but the remaining SiO2 forms a second coating layer that is too thick, which will affect the deintercalation ability of lithium ions in the substrate, and thus the fast charging and discharging capacity will be worse.
[0049] 3. It can be seen from Example 1 and Examples 8-9 that when the amount of SiO2 added is the same, when the D50 particle size of the coated substrate is changed, the surface area of the substrate will also change, thereby causing the thickness of the coating layer to change, affecting the target performance; By observing Examples 10-11 again, it can be seen that when the amount of SiO2 added remains unchanged, when the D50 particle size of the coated substrate is further increased, the remaining SiO2 forms a second coating layer that is too thick, which will affect the ability of lithium ions to be inserted and removed from the substrate, resulting in worse charge and discharge capacity; when the D50 particle size of the coated substrate is further reduced, the particle size is too small to withstand the internal stress under rapid charge and discharge, thereby affecting the performance of the ternary positive electrode material.
[0050] 4. It can be seen from Example 1 and Example 12 that when the M element in the ternary precursor replaces the Ti element with the Zr element, the prepared ternary cathode material has better capacity performance and cycle performance than Example 1 except for a slight disadvantage in the amount of residual lithium; By observing Example 13 again, it can be seen that when the ternary precursor does not contain the M element, its performance in charge and discharge capacity is similar, but since there is no M element to stabilize the crystal structure of the material, the cycle performance of the prepared ternary positive electrode material deteriorates.
[0051] Further observing Example 14, the M element is not doped in the precursor, but is added together with the metal hydroxide during the pre-sintering process for doping. From the data in Table 1, it can be seen that although the cycle performance is improved compared with Example 13 when no M element is added, it is still not as good as in-situ doping in the ternary precursor, because in-situ doping can improve the uniformity of doping, completely incorporate into the crystal structure to enhance the interface bonding strength, and better ensure the cycle stability and thermal stability of the fast-charging and fast-discharging ternary positive electrode material.
[0052] 5. It can be seen from Example 1 and Example 15 that when the same mass of lithium hydroxide is used to replace lithium carbonate as the lithium source, most of the residual lithium on the surface remains unreacted. This is because when lithium hydroxide is used as the raw material, the residual lithium on the surface is mainly lithium hydroxide, and lithium hydroxide may be difficult to react with silicon dioxide under the reaction conditions, resulting in most of the residual lithium on the surface remaining unreacted and unable to obtain an effective coating layer, resulting in poor performance of the prepared ternary positive electrode material.
[0053] 6. It can be seen from Example 1 and Example 16 that when magnesium hydroxide is used instead of sodium hydroxide to complete the doping and generate the matrix for coating, the ternary positive electrode material obtained is very close to that of Example 1 in terms of cycle performance, but in terms of charge and discharge capacity, the effect of using magnesium hydroxide as the metal hydroxide is better; Further observation of Example 17 shows that when the matrix does not contain metal hydroxide, it has only a slight effect on the cycle performance of the prepared ternary positive electrode material. However, since the metal in the metal hydroxide can occupy the Li layer, widen the Li channel, and enhance the fast charging and discharging ability of the material, its fast charging and discharging capacity shows a downward change when no metal hydroxide is added.
[0054] 7. It can be seen from Example 1 and Example 18 that when the ternary positive electrode material, lithium source, and metal hydroxide are mixed and then pre-sintered, they are directly cooled after sintering at a maximum temperature of 900°C. Since they are not kept warm at 700°C, some lattice defects caused by the high-temperature sintering of the material cannot be repaired well, further affecting the performance of the ternary positive electrode material, especially the cycle performance.
[0055] 8. Combining Example 1 with Examples 19-20, Figure 4It can be seen that no matter whether Li2CO3 and SiO2 are mixed in a molar ratio of 4:3 or 7:3 for reaction, when the temperature is less than 350°C, the mass of Li2CO3 and SiO2 in the mixture does not change significantly, but after the temperature is greater than 350°C, especially after 400°C, the mass of Li2CO3 and SiO2 in the mixture decreases rapidly. It can be seen that Li2CO3 and SiO2 need to react and the sintering temperature should be greater than 350°C; when the sintering temperature is higher than 500°C, the thermal motion of lithium atoms in the lattice intensifies, and their activity increases significantly, making it easier to overcome the constraints of lattice energy and deintercalate from the lattice, resulting in the obtained ternary positive electrode material being relatively poor in residual lithium and performance.
[0056] 9. By comparing Example 1 with Comparative Example 1, the content of Si element used in the formation of the Li2Si2O5 coating layer can be calculated from the change in residual lithium between the substrate of Example 1 and the ternary positive electrode material prepared in Example 1; When the Si element content remains unchanged, in Comparative Example 1, disilicate with the same Si element content as that of the ternary positive electrode material Li2Si2O5 coating layer as in Example 1 is used to react with residual lithium on the surface to form a first coating layer, and the remaining Si element is directly coated in the form of SiO2 to form a second coating layer. However, it can be seen from Table 1 that, under the same structure, the double-coated ternary positive electrode material (i.e., Example 1) obtained by direct one-step coating with SiO2 has better performance, while the double-coated ternary positive electrode material obtained by two-step coating in Comparative Example 1 is due to the lattice lithium being released during the two-step coating process, resulting in uncontrollable residual lithium on the surface, resulting in the ternary positive electrode material obtained having poor control of residual lithium and electrical properties.
[0057] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principles of the present invention shall be equivalent replacement methods and shall be included in the protection scope of the present invention.
Claims
1. A ternary positive electrode material, characterized in that: The ternary positive electrode material is composed of a substrate, a first coating layer coated on the surface of the substrate, and a second coating layer coated on the surface of the first coating layer; The first coating layer is a Li2Si2O5 coating layer; The second coating layer is a SiO2 coating layer; The first coating layer is formed by the reaction of SiO2 and residual lithium on the surface of the substrate; The second coating layer is formed by the SiO2 remaining from the reaction of the first coating layer with the residual lithium on the surface of the substrate.
2. The ternary positive electrode material according to claim 1, characterized in that: The specific operation of forming the first coating layer and the second coating layer is: putting SiO2 and the substrate into a mixer for mixing, and then sintering, cooling, crushing, and sieving to obtain a ternary positive electrode material containing a double coating layer; The mass of Si element in the SiO2 is 0.3% to 0.5% of the mass of the matrix; The D50 particle size of the matrix is 5 to 8 μm.
3. The ternary cathode material according to claim 2, characterized in that: The rotating speed of the mixer is: firstly rotate at 20-100 rpm for 5-10 min, and then rotate at 500-800 rpm for 15-25 min.
4. A method for preparing a ternary positive electrode material according to any one of claims 1 to 3, characterized in that: The following steps are involved: Step 1: Mixing, pre-sintering, cooling, crushing and screening the ternary precursor, lithium source and metal hydroxide to obtain a matrix; Step 2: Put SiO2 and the matrix into a mixer for mixing, and then sinter, cool, crush and sieve to obtain a ternary positive electrode material containing a double coating layer.
5. The preparation method according to claim 4, characterized in that: The ternary precursor is Ni x Co y Mn z M 1-x-y-z (OH)2, of which 0.5 <x<0.65,0.2<y<0.3,0.045<z<0.295; The M element is selected from Ti, Zr, Ce, Sn or W elements.
6. The preparation method according to claim 4, characterized in that: The lithium source is lithium carbonate, and the molar ratio of lithium element in the lithium source to the metal element in the ternary precursor is 1.01 to 1.10; The metal hydroxide is selected from at least one of sodium hydroxide, magnesium hydroxide and aluminum hydroxide, and the mass of the metal element is 1000-2000ppm of the mass of the ternary precursor.
7. The preparation method according to claim 4, characterized in that: The specific operation of the pre-sintering is: firstly heating to 650-750°C at 2-5°C / min and keeping it warm for 3-5 hours; then heating to 850-950°C at 2-3°C / min and keeping it warm for 10-16 hours; then cooling to 650-750°C at 3-5°C / min and keeping it warm for 1-3 hours.
8. The preparation method according to claim 4, characterized in that: The specific steps of sintering in step 2 are: heating to 350-500° C. at 2-3° C. / min and keeping the temperature for 8-12 hours.
Citation Information
Patent Citations
High-energy density nickel-series composite positive electrode material for lithium ion battery and preparation method of high-energy density nickel-series composite positive electrode material
CN104124449A
Preparation method of coated lithium ion battery ternary positive electrode material
CN107240690A
Double layer clad lithium ion battery cathode material and preparation method thereof
CN108666534A
Nickel cobalt lithium manganate composite positive electrode material and preparation method thereof as well as lithium ion battery
CN108777295A
Carbon-coated high nickel ternary positive electrode material and preparation method therefor
CN108878828A